Development of ocean modelling: the Malaysian perspective - Camerlengo, Alejandro Livio (2000)
The ocean environment has been subjected to severe deterioration in the past few decades. This worsening situation is attributed mainly to the extensive use of pesticides in coastal areas, the rapid expansion of vast metropolitan areas and the displacement of industries to the coastal areas. At the same time, given the rising cost of energy, reckless offshore dumping of industrial wastes has increased. All these have contributed greatly to the fouling of the ocean environment. Concomitantly, harvesting of marine products for providing food to the increasing global population is on the rise. In particular, over-fishing of demersal stocks has been observed in Peninsular Malaysia eastern coast (Ambak et al., 1981; Ambak and Mohsin, 1982; Ambak and Harmin, 1982; Ambak, 2000). There is an increasing need to manage the ocean environment and to explore for meaningful compromises between the demands of growing industrialization and emergence of prosperous societies and the need to maintain the natural resources. This represents an optimal control problem that canm only be addressed by numerical models.